INVESTIGATING FORMATIVE ASSESSMENT - Tashpulatova , Nafisa Bakhtiyorovna (Innovative Development in Educational Activities, 2024)
In this paper, the author defines formative assessment and elaborates readers’ understanding of the term. The central role of formative assessment to motivate language learners in the teaching and learning process is highlighted. Formative and summative assessment with a clear example of personal experience is illustrated. The writer explains how teachers in two distinct cultures approaches to student learning.